KAJIAN TEORITIS RELASI DAN KEPENTINGAN ELIT LOKAL PARTAI DI ERA OTONOMI - Yusuf Wibisono; Zainul Djumadin (Universitas Nasional, 2020)
The era of regional autonomy not only gave birth to a new government system, but also gave birth to the dynamics of elite circulation in an increasingly complicated area, especially for political party elites. The emergence of the term